Developing A Self-Sufficiency Economy Through Islamic Solidarity Economy (ISE) Model For Sustainable Economy And Resilient Local Community Comparative Perspectives Between Malaysia And Indonesia - Robani, Anidah; Ahamat, Amiruddin; Syed Hassan, Syed Najmuddin; Kamarudin, Mohd Fauzi; Ahmat, Norun Najjah; Omar, Siti Rohana; Md Saad, Mohd Shamsuri (UTeM, 2019)
Although sustainable development issues have been an important research topic for several decades, very little research has focused on the issues at the local level particularly in developing countries. Compared to sustainable development within developed economies, Asian communities particularly Malaysia have far less awareness and rigorous approach towards maximizing the potential of Islamic Solidarity Economy in enhancing sustainable development at the local level. This study suggests that this ISE model can be the best alternative system for development in this post-capitalist development agenda The objective of this article is therefore, to explore the potential of Islamic Solidarity Economy in relation to sustainable development at the local level. This article considers how Islamic Solidarity Economy can contribute in enhancing sustainable development at the local level, based on an analysis of the documentary evidence provided by theoretical perspectives and empirical studies. The central argument of this article revolves around the idea that Islamic Solidarity Economy with its focus on social justice (‘adl), balance (mizan), and common good (maslahah a’mmah) can be the best alternative system in this post-capitalist development agenda. The objective of this study is twofold. First, it attempts to explore the significance and potential of Islamic Solidarity Economy as an alternative economic paradigm and development model. Secondly, this study addresses the implementation of Islamic Solidarity Economy at the local level with pondok and pesantren in Malaysia and Indonesia as case studies. This study highlights that social entrepreneurship may strengthen the role of Islamic Solidarity Economy in enhancing sustainable economy and resilient community at the local level.